2018
DOI: 10.1103/physreve.97.042501
|View full text |Cite
|
Sign up to set email alerts
|

Crystallization in melts of short, semiflexible hard polymer chains: An interplay of entropies and dimensions

Abstract: What is the thermodynamic driving force for the crystallization of melts of semiflexible polymers? We try to answer this question by employing stochastic approximation Monte Carlo simulations to obtain the complete thermodynamic equilibrium information for a melt of short, semiflexible polymer chains with purely repulsive nonbonded interactions. The thermodynamics is obtained based on the density of states of our coarse-grained model, which varies by up to 5600 orders of magnitude. We show that our polymer mel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
41
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(41 citation statements)
references
References 59 publications
0
41
0
Order By: Relevance
“…We numerically estimate the entropy, , of the system by the SAMC method [ 15 , 16 , 17 , 18 ]. The micro-canonical entropy defines the logarithm of the density of states (DOS) of the system .…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…We numerically estimate the entropy, , of the system by the SAMC method [ 15 , 16 , 17 , 18 ]. The micro-canonical entropy defines the logarithm of the density of states (DOS) of the system .…”
Section: Methodsmentioning
confidence: 99%
“…The semi-flexible tangent hard-sphere chain is a simplified model of real polymers. We calculated previously, by means of stochastic approximation Monte Carlo (SAMC) simulation [ 15 , 16 , 17 ], the micro-canonical entropy of a dense semi-flexible tangent hard-sphere polymer system [ 18 ] (we provide a more detailed description of the model in Section 2 ). When the system is big enough, the model polymer melt undergoes an ordering transition into a layered rotator-like phase, which is similar to the rotator phases of n-alkanes: a family of smectically ordered phases with different ordering in layers [ 19 , 20 , 21 , 22 ].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Recently, it has been demonstrated that dense packing of chains of hard spheres also crystallize [43][44][45][46]. It is possible to effectively control the phase behavior and/or the state of jamming [47][48][49][50] for polymers by properly tuning the bond gaps (or bond tangency) between successive monomers along the chain [51,52] or the bending angles that dictate chain flexibility [53,54]. Similar control can be achieved by applying spatial confinement; in the most trivial case this can be realized through the presence of flat, impenetrable, and parallel walls in at least one dimension.…”
Section: Introductionmentioning
confidence: 99%